Equipping Civil Technology Teachers with Hands-On Skills and Educational Resources for Effective Teaching of Practical Lessons - Msimango, Simphiwe Magnificent; Mtshali, Thokozani Isaac; Khoza, Samuel Dumazi (Research in Social Sciences and Technology- OpenED Network, 2024)
Continuous professional development for teachers will always be prioritized, especially in cases where there are obvious and conspicuous gaps in their subject-matter expertise and when they handle practical skills exercises with inadequate planning and delivery. Hence, this study explores the effects of equipping Civil Technology teachers with hands-on skills and provision of educational resources for effective teaching of practical lessons. This study purposefully sampled nine (09) Civil Technology teachers from Ekurhuleni East, Gauteng province of South Africa. This study was hinged on Stronge’s qualities of effective teachers as its framework. This study adapted a mixed method design where closed-ended questionnaires and semi-structured interviews were considered relevant data collection instrument and sources. A sequential explanatory design was used to analyze the collected data. The findings reveal that even though teachers get continuous hands-on skills training from the Gauteng Department of Education (GDE) annually, the trainings are often too generic and do not adequately boost teachers with confidence to teach specific skills (i.e., construction and plumbing) to learners. As a result, Civil Technology teachers could not actualize their continuous professional development training as an element of learning to become innovative skills teachers. The survey found that while certain Ekurhuleni East schools have instructional tools, some of the teachers were not trained to use them, which made it difficult to effectively teach practical lessons in Civil Technology. Therefore, this study recommended that the Gauteng Department of Education should focus on discipline specific instructional strategies that will promote innovation in skills-based activities in Civil Technology.